Pinocula - Skye, Obert (Skye, Obert. Creature from my closet, 2017)
Things are going pretty well for Rob Burnside until Pinocula--a cross between Pinocchio and a vampire--emerges from his closet, lying, joking, and doing his best to drive Rob crazy.